Under the radar: the danger of stealthy DDoS attacks. Issue 2 (February 2019) - Newman, Sean
Abstract : Despite several headline-dominating, high-volume distributed denial of service (DDoS) attacks over recent years, the majority of attack attempts continue to be short in duration and low in volume. Such attacks have unnervingly high success rates due to their stealthy nature and their ability to slip in completely unnoticed, often masked by the organisation's regular traffic flow. These attacks are fast and brief, leaving security teams with little time to react – and that's assuming they're able to detect the attack at all.